Pengaruh Employee Engagement, Spiritualitas Kerja, Budaya Organisasi Terhadap Kinerja Karyawan Dimoderasi Kepemimpinan Kepala Sekolah - H. Franky Ari Andriprianto; Herry Maridjo (Unika Santu Paulus Ruteng, 2022)
Schools as student-oriented educational institutions are service centers. All resources are directed to provide optimal services in the student learning process. Therefore, the performance of employees (teachers and education personnel) in schools needs to be improved. This study aims at determining the effect of employee engagement, work spirituality, and organizational culture on employee performance with the principal's leadership as a moderating variable. The population in this study was all employees of SMA Kolese de Britto. The sample in this study was 73 employees taken by using proportional clustered random sampling. Data analysis using the SEM-PLS method with the help of SMARTPLS v.3.0 software was utilized. The results of the analysis indicate that employee engagement and work spirituality have a positive and significant effect on employee performance variables. Meanwhile, organizational culture has no effect on employee performance and principal leadership variable do not moderate the effect of employee engagement, organizational culture, and work spirituality on employee performance